Influence of estradiol cypionate on the resumption of postpartum ovarian activity in Holstein dairy cows under an intensive rearing system in the northern coast of the Lima dairy basin - Medrano Rueda, Patricia Luisa (2024)
The influence of the synthetic estrogen estradiol cypionate (EC) on the resumption of postpartum ovarian activity was evaluated in Holstein dairy cows raised under an intensive system in the northern coast of the Lima dairy basin. Twenty multiparous Holstein cows were selected, and ovarian activity was monitored by ultrasonography, and blood samples were collected to measure serum progesterone every other day from day 5 postpartum until day 60. Cows were randomly assigned to two groups: EC (n = 10), which received an intramuscular dose of 2 mL EC (4 mg, ECP®, Zoetis, USA) at 7 days postpartum; and a control group (n = 10), which received no treatment. Descriptive and inferential statistical analyses were performed. Dependent variables included the calving-to-first-ovulation interval and serum progesterone levels, while independent variables were the diameter of the first postpartum preovulatory follicle and the diameter of the first postpartum corpus luteum at 10 days after ovulation. The control group showed a larger diameter of the first postpartum corpus luteum at 10 days post-ovulation (p < 0.05) compared with the EC group (24.73 ± 5.51 vs. 19.04 ± 6.07, respectively). In addition, a positive correlation was found between serum progesterone levels and corpus luteum diameter at 10 days post-ovulation in the experimental group (rs = 0.83; p = 0.01). It is concluded that the resumption of postpartum ovarian activity in cows exposed to EC is similar to the control group, according to the variables that characterize the restoration of cyclicity.